BETTY FREUND: A NURSE IN FRANCE - Part I - Hugo, Betty (Scientia Militaria - South African Journal of Military Studies, 2012)
Betty Freund was the eldest child of John and Metha Freund (nee Menzel), both from Germany, who met in Philippolis, OFS, where they were married in the late 1870's. Betty was born in 1881. Then followed her sister Mimie (1883), and her brothers Freddy (1885) and Willy (1887). The family went to Germany a few years after Willy was born, settling in GIOcksburg, Metha Freund's home town. The youngest child, Mina, was born there. By 1894 the Freunds had returned to Luckhoff where Metha's brother Wilhelm Menzel had been looking after their interests, but during the Anglo-Boer War the family moved to Cape Town where they lived, first, in Livingston Villa in Cecil Street, Claremont, and subsequently in Lansdown Road, also in Claremont, in a house called ZOrenborg. The children had been to school in Luckhoff and GIOcksburg; Freddy and Willy matriculated at the Rondebosch Boy's High School, Betty and Mimie at Bloemhof Girl's High School in Stellenbosch, and Mina in Edinburg, Scotland, after having attended Milburn House in Cape Town.